Evaluation of Radiopacity of Endosequence Bio-ceramic Sealer and AH Plus by Digital Radiography - Saima Qureshi; Feroze Ali Kalhoro; Haresh Oad; Muhammad Ali Panhwar; Faryal Manzoor; Fahad Aslam Shujrah (Pakistan Journal of Health Sciences, 2026)
Radiopacity is a key requirement for endodontic sealers to allow radiographic distinction between obturation material and surrounding tooth structures. American National Standards Institute (ANSI) and American Dental Association (ADA) mandate a minimum of 3 millimetres of aluminium (mm Al). Objectives: To compare, in vitro, the radiopacity of Endo-Sequence BC Sealer versus AH Plus using digital radiography on extracted human single-rooted teeth. Methods: An experimental in vitro study was conducted at the Department of Operative Dentistry, Liaquat University of Medical and Health Sciences, Jamshoro. A total of 60 single‑rooted teeth were selected using a non-probability convenience sampling method and allocated into two groups (n=30 each) without randomization. Care was taken to ensure that the two groups were comparable in terms of tooth type and root morphology and obturated with gutta-percha plus either Endosequence BC or AH Plus. After 7 days at 37°C/100 % humidity, radiopacity was expressed as millimetres of aluminium (mm Al). Data were compared using an independent-samples t-test (α = 0.05). Results: The sample analyzed consisted of 60 samples (30 samples per group). AH Plus demonstrated significantly higher radiopacity (6.94 ± 0.46 mm Al) compared to Endosequence BC (3.83 ± 0.35 mm Al). The confidence intervals were not overlapping (AH Plus: 6.77 7.10 mm Al; Endosequence BC: 3.71 ± 3.96 mm Al). The difference was statistically very significant (p